Optimization of Cadmium Removal Using Tetraethylene Glycol-Modified Silica-Based Adsorbent via Response Surface Methodology - Roza Linda; Abdullah Abdullah; Afrianto Daud; Lisa Aprilia Indriyani; Lee Wah Lim; Henny Purwaningsih; Mohamad Rafi (Jurnal Kimia Sains dan Aplikasi, 2024)
In solid-phase extraction for preconcentration, silica (Si) is the most commonly used as an adsorbent. However, the selectivity and effectiveness of silica gel adsorption on metal ions are low, so it needs to be modified to improve the adsorption capability. The modification was done using reflux and oven heating in the modification silica with 3-glycidoxypropyl trimethoxysilane (GPTMS) and tetraethylene glycol (TEG). A central composite design batch process determined the optimum conditions for cadmium adsorption. TEG-modified silica was successfully synthesized and characterized using FTIR spectroscopy, SEM, and elemental analyzers. Peaks of C-H and epoxy on FTIR spectra showed that Si- GPTMS was formed. The increase of %C and %H from the first to the second step indicated that Si-TEG was successfully synthesized. There was no significant difference in silica particle morphology on SEM before and after modification. The reflux method gave a higher yield compared to the heating method. The constant stirring by the magnetic bar and solvent cycle in the reflux method catalyzed the reaction. This study found that at pH 7, 30 mg of adsorbent weight at 35°C and 22 minutes of contact time were optimum Cd2+ adsorption conditions. As the weight of the adsorbent increases, the adsorption capacity decreases. Contact time and temperature have no significant effect on Cd adsorption by Si-TEG.